Identifikasi Komoditas Unggulan Pertanian dalam Mendukung Kawasan Agropolitan Studi Kasus: Kecamatan Pasaleman, Kabupaten Cirebon - Fika Novitasari; Rintakasari Vitri Ayuningtyas (P4W LPPM IPB, 2018)
The development direction of Ciledug Agropolitan Area based on Cirebon Regency Spatial Plan 2011-2031 covers five districts: Pasaleman District, Waled District, Babakan District, Pabedilan District, and Pabuaran District. Each district has a role to support the system of Ciledug Agropolitan Region. Pasaleman District has a role as a producer of agricultural products in Ciledug Agropolitan Area, thus the district has an urgency to discover potential commodities that can be developed in order to support the development of Ciledug Agropolitan Area. The objective of this research is to identify leading agricultural commodities in Pasaleman District in order to support the role of Pasaleman District as agropolitan area. Stages to achieve the objectives are to study the concept of agropolitan area, to identify methods in determining leading agricultural commodities, to identify of leading commodities in Pasaleman District, and to determine the role of Pasaleman District towards Ciledug Agropolitan Area system. Data collection method in this research uses secondary data and primary data from farmer questionnaire in Pasaleman District with Slovin method for sampling. In this study, four methods of analysis is used in order to identify the leading agricultural commodities in Pasaleman District: Location Quetient (LQ), agricultural productivity, agricultural production, and profit of each commodity. Results from production and productivity calculation shows that the leading agricultural commodity in Pasaleman District is sugarcane. However, the results of LQ and profit calculation show that the leading agricultural commodity in Pasaleman District is papaya. The implications of this study are expected to contribute in policy formulation for local governments and farmers in developing the leading agricultural commodities in Pasaleman District.